Search for $W' → tb$ in proton-proton collisions at $\sqrt{s} = $ 8 TeV - CMS collaboration (2283 authors) (2016)
A search is performed for the production of a massive W′ boson decaying to a top and a bottom quark. The data analysed correspond to an integrated luminosity of 19.7 fb$^{−1}$ collected with the CMS detector at the LHC in proton-proton collisions at $ \sqrt{s}=8 $ TeV. The hadronic decay products of the top quark with high Lorentz boost from the W′ boson decay are detected as a single top flavoured jet. The use of jet substructure algorithms allows the top quark jet to be distinguished from standard model QCD background. Limits on the production cross section of a right-handed W′ boson are obtained, together with constraints on the left-handed and right-handed couplings of the W′ boson to quarks. The production of a right-handed W′ boson with a mass below 2.02 TeV decaying to a hadronic final state is excluded at 95% confidence level. This mass limit increases to 2.15 TeV when both hadronic and leptonic decays are considered, and is the most stringent lower mass limit to date in the tb decay mode.